THE IMPLEMENTATION OF AUTONOMOUS ONLINE LEARNING TO ENHANCE ACADEMIC WRITING COMPETENCE DURING COVID-19 PANDEMIC - Sukma Nur Ardini; Hernaning Tyas Saputri (Journal of English Educational Study (JEES), 2022)
Autonomous learning during covid-19 pandemic situation becomes the best strategy to perform an effective learning process. Particularly, autonomous learning in academic writing course requires great deals of students’ willingness to manage their time and ability. This paper is a content analysis which aims to analyze the implementation of autonomous learning strategy. Descriptive qualitative method was used to investigate and describe how 20 higher education students managed their time and ability as well as to find out the obstacles. In collecting the data, the researchers used questionnaire and interview. Students had implemented autonomous learning in various ways. They practicedwriting independently by completing the tasks and assignments given by the lecturer. They also used internet to find sources such as online translator, education websites, and explanation videos on YouTube. Some obstacles were occurred during autonomous online Academic Writing due to some reasons; such as; 1) poor internet connection, 2) lack of competence in understanding academic writing materials through online learning which needs more effort such as creating group discussion among classmates, 3) weakness in building keywords when they tried to search terms used in Academic Writing course.